Some remarks on the invariant subspace problem for hyponormal operators - Vasile Lauric (International Journal of Mathematics and Mathematical Sciences)
We make some remarks concerning the invariant subspace problem for hyponormal operators. In particular, we bring together various hypotheses that must hold for a hyponormal operator without nontrivial invariant subspaces, and we discuss the existence of such operators.